Synergistic Antibacterial Activity of Benzalkonium Bromide and Cu-Bearing Duplex Stainless Steel against Pseudomonas aeruginosa - Xiaomeng Liu; Chengshuo Qiu; Mingxing Zhang; Enze Zhou; Dake Xu; Yongqiang Fan; Yongbo Song (Microorganisms, 2023)
The bactericide benzalkonium bromide is widely used to kill Pseudomonas aeruginosa, which causes microbiologically influenced corrosion (MIC). However, the extensive use of benzalkonium bromide will enhance bacterial drug resistance and cause environmental pollution. In this study, benzalkonium bromide combined with Cu-bearing 2205 duplex stainless steel (2205-Cu DSS) was used to kill Pseudomonas aeruginosa; the germicidal rate of the combination of benzalkonium bromide and 2205-Cu DSS was 24.2% higher than that of using benzalkonium bromide alone, after five days. The antibacterial efficacy was evaluated using an antibacterial test and biofilm observation. The results showed that, in the presence of P. aeruginosa, the combination of 23.44 ppm benzalkonium bromide and 2205-Cu DSS showed the best antibacterial efficacy.